Literature review: state-of-the-art hydrogen storage technologies and Liquid Organic Hydrogen Carrier (LOHC) development - D’Ambra Florian; Gébel Gérard (Science and Technology for Energy Transition, 2023)
Greenhouse gas anthropogenic emissions have triggered global warming with increasingly alarming consequences, motivating the development of carbon-free energy systems. Hydrogen is proposed as an environmentally benign energy vector to implement this strategy, but safe and efficient large-scale hydrogen storage technologies are still lacking to develop a competitive Hydrogen economy. LOHC (Liquid Organic Hydrogen Carrier) improves the storage and handling of hydrogen by covalently binding it to a liquid organic framework through catalytic exothermic hydrogenation and endothermic dehydrogenation reactions. LOHCs are oil-like materials that are compatible with the current oil and gas infrastructures. Nevertheless, their high dehydrogenation enthalpy, platinoid-based catalysts, and thermal stability are bottlenecks to the emergence of this technology. In this review, hydrogen storage technologies and in particular LOHC are presented. Moreover, potential reactivities to design innovative LOHC are discussed.